Clinical and molecular predictors of long-term response in HER2 positive metastatic breast cancer patients. Issue 10 (3rd October 2018) - Omarini, Claudia; Bettelli, Stefania; Caprera, Cecilia; Manfredini, Samantha; Caggia, Federica; Guaitoli, Giorgia; Moscetti, Luca; Toss, Angela; Cortesi, Laura; Kaleci, Shaniko; Maiorana, Antonino; Cascinu, Stefano; et al.
ABSTRACT: Background : HER2+ metastatic breast cancer (MBC) is a poor prognosis disease, unusually curable. To date, no predictive factors have been clearly correlated with long-term response to anti-HER2 agents. Methods : 54 HER2+ MBC patients treated with HER2 targeted therapy as first line treatment were analysed: 40 with a time to progression longer than 3 years in Long Responders (LR) group and 14 with a progression disease within one year of anti-HER2 therapy in a control group named Early Progressors (EP). The expression of 770 genes and 13 molecular pathways were evaluated using Nanostring PanCancer pathway panel performed on FFPE BC tissues. Results : Considering baseline patients and tumor characteristics, EP women had more CNS spread and more metastatic burden of disease compared to LR (p > 0.05). Gene expression analysis identified 30 genes with significantly different expression in the two cohorts; five were driver genes (BRCA1, PDGFRA, AR, PHF6 and MSH2). The majority of these genes were over-expressed, mainly in LR patients, and encoded growth factors, pro- or anti-inflammatory interleukins and DNA repair factors. Only four genes were down regulated, all in EP group (TNFSF10, CACNG1, IL20RB and BRCA1). Most of these genes were involved in MAPK and PI3K pathways. MAPK pathway was differently expressed between LR and EP (p = 0.05). PI3K was the only pathway overexpressed in EP patients. Conclusions : Whole genome expression analysis comparing LR vs. EP identified a group of genes that may predict more favourable long-term outcomes. Up-regulation of MAPK and down-regulation of PI3K pathway could be a positive predictive factors. Further clinical implications are warranted. Abbreviations : BC: breast cancer; MBC: metastatic breast cancer; LR: long responder; EP: early progressor; FFPE: formalin-fixed paraffin-embedded; CNS: central nervous system; PFS: progression free survival; OS: overall survival.